From Logic to Functional Logic Programs. Issue 4 (4th July 2022) - HANUS, MICHAEL
Abstract: Logic programming is a flexible programming paradigm due to the use of predicates without a fixed data flow. To extend logic languages with the compact notation of functional programming, there are various proposals to map evaluable functions into predicates in order to stay in the logic programming framework. Since amalgamated functional logic languages offer flexible as well as efficient evaluation strategies, we propose an opposite approach in this paper. By mapping logic programs into functional logic programs with a transformation based on inferring functional dependencies, we develop a fully automatic transformation which keeps the flexibility of logic programming but can improve computations by reducing infinite search spaces to finite ones.